A legeltetéses állattenyésztés meghonosításának lehetőségei és korlátai Somogy megyében - Bokorné Kitanics, Tünde (Tér és Társadalom, 1996)
Approximately two thirds of the territory of Somogy county is hilly areas. The average of the slopes of the county is 8-11%. Compared to the large regions of Hungary, South Transdanubia has the most precipitation, also, its distribution is the most balanced here. Somogy county is one of the regions in Hungary which have the best ecological endowments for pasturage. Because of the characteristic hilly surface of the county, a rational land use is necessary. In the case of a right land use, the more steep a slope, the smaller the share of plough-land and the larger the share of forest, pasture and meadow. The ideal case would be if grass were dominant on slopes of 17-25% and forests on slopes steeper than 25%. In the territory of Somogy county, large-scale plough-lands can be found on poor quality, steep hillsides. I suggest that grassy areas be planted to replace the plough-lands which have a low fertility. Grass plays an important role in the exchange of lands. The cultivation of steep plough-lands abounds in difficulties, there is a great danger of soil erosion, also, crops are'smaller than in plain lands. On slopes, grass is the best protector of the soil. On the slopes and hillsides, a profitable grazing animal husbandry can be implemented with the right skills and cultivation. The ecological potential of Somogy county is under-utilised, as both the number of grassy areas and grazing animals is decreasing. For private entrepreneurs, cattle breeding could provide a certain living. The traditional way of using the pastures is sheep breeding, which can utilise the larger and less fertile pastures, as well. A specific way of using the grassy lands is breeding horse for its meat. The extremely weak pastures could be grazed by red and fallow deer. The decreasing and derelict grassy areas are still reserves for the Hungarian agriculture. These grassy areas, however, should not be taken out of cultivation but should help us to rationalise agriculture, animal breeding, fodder production and to improve the profitability of producing animal products.